EFEKTIVITAS PENDAMPINGAN DESA DAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN INFRASTRUKTUR PEDESAAN DI DESA SEKODI KECAMATAN BENGKALIS KABUPATEN BENGKALIS - Susanti, Rezky; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Rural infrastructure development in the Sekodi Village of Bengkalis District that through with one of local government programs in Bengkalis Regency than knowns as Regent Instruction Strengthening Rural Infrastructure Program “INBUP-PPIP” which aims to support efforts to tackle poverty and underdevelopment in rural infrastructure in Bengkalis, so as to more increase community empowerment in the development, the power rural assistance village known as Village development Assistants to provide guidance, coaching, and supervision and management of existing development activities in the village administration in particular the implementation of INBUP-PPIP and community participation is needed in determining the direction of and development priorities in order to achieve a common goal.The author takes the phenomenon of research on the effectiveness of Rural Assistance and community participation in rural infrastructure development to determine the public's assessment of the effectiveness of Rural Assistance, as well as public participation in the development of rural infrastructure in the Sekodi village, this study used a quantitative descriptive analysis and establish a sample of 71 people Head Families (HF) were taken from every Cluster in the village sekodi namely: Cluster in Tanjung sekodi 15% x197HF= 30 people, 15% Cluster in Nyatuh x169 HF = 25 people, cluster in Permai 15% x 109 HF = 16 people.The results showed that, People consider that Rural Assistance still less effective that show in terms of presence on duty in the village, facilitation of planning, implementation, monitoring, communication, still considered less good, although that some people have assessed the development of socialization, planning assistance, ability, and responsibility, results in the presence of a companion rural development in the construction of the village was considered quite good companion, even the public judge for sustainability of care in the village is still part of the population (respondents) who agreed to 45.1% and the others were agreed 45.1% and 9.9% did not agree. while participation in the development of rural infrastructure in sekodi Village still moderate that show of participation in the meetings, mutual assistance, self-power, responsibility,supervision, delivery cheating, keep the fruits of development, utilization of the results, as well as overseeing the development was considered quite active, although the submission of ideas (the proposed development), self-funding, self-help materials assessed to be less active.Keywords: Rural Assistance, Participation, Infrastructure Development